2007
DOI: 10.1107/s1600536807066810
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylammonium bis(3-oxidonaphthalene-2-carboxylato)borate hemihydrate

Abstract: The title compound, C2H8N+·C22H12BO6 −·0.5H2O, was synthesized under atmospheric conditions in the presence of dimethyl­formamide acting as a template. The structure is composed of [NH2(CH3)2]+ cations, bis­(3-oxidonaphthalene-2-carboxyl­ato)borate anions and water mol­ecules. The water molecule lies on a twofold rotation axis. The stabilization of the crystal structure comes from electrostatic inter­actions and is assisted by inter­molecular O—H⋯O and N—H⋯O hydrogen bonds between the layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The sp 3 -hybridized B atom is bonded to four O atoms to form a distorted tetrahedral environment where the B-O(phenolate) bond lengths (to atoms O1 and O3; Tables 2 and 3) are shorter than the B-O(carboxylate) bond lengths (to atoms O2 and O4; Tables 2 and 3). These observed bondlength variations have been explained in terms of electrostatic valence principles (Pauling, 1929) to relate bond strength to B-O bond length (Li & Liu, 2006;Cody, 1984;Zviedre et al, 1999;Zachariasen, 1963), and are in close agreement with values reported previously [B-O(hydroxy) = 1.445 and 1.459 Å , and B-O(hydroxy of carboxy) = 1.472 and 1.483 Å (Yang et al, 2011); B-O(hydroxy) = 1.427 (5) and 1.426 (5) Å , and B-O(hydroxy of carboxy) = 1.496 (5) and 1.502 (5) Å (Tombul et al, 2008)]. The O-B-O angles are in the range 105.24 (15)-113.45 (16) in (1) and 106.79 (13)-113.28 (14) in (2) (Tables 2 and 3).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The sp 3 -hybridized B atom is bonded to four O atoms to form a distorted tetrahedral environment where the B-O(phenolate) bond lengths (to atoms O1 and O3; Tables 2 and 3) are shorter than the B-O(carboxylate) bond lengths (to atoms O2 and O4; Tables 2 and 3). These observed bondlength variations have been explained in terms of electrostatic valence principles (Pauling, 1929) to relate bond strength to B-O bond length (Li & Liu, 2006;Cody, 1984;Zviedre et al, 1999;Zachariasen, 1963), and are in close agreement with values reported previously [B-O(hydroxy) = 1.445 and 1.459 Å , and B-O(hydroxy of carboxy) = 1.472 and 1.483 Å (Yang et al, 2011); B-O(hydroxy) = 1.427 (5) and 1.426 (5) Å , and B-O(hydroxy of carboxy) = 1.496 (5) and 1.502 (5) Å (Tombul et al, 2008)]. The O-B-O angles are in the range 105.24 (15)-113.45 (16) in (1) and 106.79 (13)-113.28 (14) in (2) (Tables 2 and 3).…”
Section: Resultssupporting
confidence: 92%
“…The structures of these compounds can be represented in a binary fashion as consisting of an anionic borate structural unit and a cationic interstitial complex. In borate minerals, boron forms strong bonds with oxygen in trigonal BO 3 and tetrahedral BO 4 units which are able to polymerize, via corner-sharing of the O atoms, into larger polynuclear anionic units, including isolated or finite clusters, chains, sheets and networks (Grice et al, 1999), while the tetrahedral BO 4 group may share O atoms to form isolated rings with a variety of organic molecules (Allen et al, 2012;Yang et al, 2011;Tang & Huang, 2009;Tombul et al, 2008). The nonmetal cations meanwhile play a different role from the metal cations since they generally do not coordinate to oxygen in the same way and may act instead as hydrogen-bond donors to the structural unit.…”
Section: Introductionmentioning
confidence: 99%
“…Other applications of these particular type of compounds involve a use as catalysts, or co-catalysts, for the Diels-Alder reaction [10], methoxycarbonylation reactions [11], and in amide and ester condensation reactions [12]. As part of our ongoing study of the synthesis and structure of organoborate complexes [13][14][15][16], we have prepared a new organically templated borate using pyridine as the structure-directing agent. …”
Section: Discussionmentioning
confidence: 99%
“…7 The role of non-metal cations differs from metal cations, since they generally do not coordinate to oxygen in the same way, and may act instead as hydrogen bond donors to the structural unit. Continuation persistently our progressing work on borates, [8][9][10][11] the process of the self-assembly of organic and inorganic moieties has been performed under DMF solution conditions, and yielded original borate with organic amine, namely dimethyl ammonium bis(p-tertbutylcatecholato) borate.…”
mentioning
confidence: 99%